2019
DOI: 10.3354/meps12812
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic fish communities: sound diversity of rocky habitats reflects fish species diversity

Abstract: Assessing fish biodiversity patterns is a major concern in aquatic science and conservation. To be effectively used, fish diversity assessments benefit from the use of integrated complementary approaches. Passive acoustics has received increasing attention as a non-invasive, longterm monitoring tool, as it uses biological sounds produced incidentally or intentionally as natural tags to identify and estimate animal diversity. In the marine environment, there is little evidence about the link between taxonomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 84 publications
3
59
0
Order By: Relevance
“…Louder habitats may correlate with higher species richness and abundance [11,12]. In the present study, we showed that higher species diversity and abundance occurred during seasonal periods (i.e.…”
Section: Soundscape and Biodiversitysupporting
confidence: 55%
See 1 more Smart Citation
“…Louder habitats may correlate with higher species richness and abundance [11,12]. In the present study, we showed that higher species diversity and abundance occurred during seasonal periods (i.e.…”
Section: Soundscape and Biodiversitysupporting
confidence: 55%
“…Applications to marine ecosystems are more challenging but evidence suggests that sound diversity can reflect species diversity (i.e. measured by underwater visual census of fish) in mangrove, coral reef, seagrass, and rocky habitats [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A 16-month follow-up study at additional Pacific Ocean sites showed similar patterns [ 7 ]. Desiderà et al [ 107 ] found a relationship between sound types (not indices) and taxonomic diversity. They compared years of visual census data from a Mediterranean Sea MPA to acoustic data and found a strong relationship between taxonomic diversity and acoustic diversity (but not acoustic indices).…”
Section: Initial Methods and Challenges In Assessing Aquatic Acousticmentioning
confidence: 99%
“…While many sources of these biological sounds have been identified, a larger proportion are still unconfirmed. All, however, contribute to the diversity of the soundscape and provide important information on the location's biodiversity [ 107 ]. These calls may be produced rarely, with no temporal pattern, or in series, often with a distinct temporal pattern, depending on their function.…”
Section: Considerations For Using Acoustic Methods To Estimate Marinementioning
confidence: 99%
See 1 more Smart Citation